Genotypic detection of β-lactamase-producing Escherichia coli isolates obtained from Seven Crater Lakes of San Pablo, Laguna, Philippines - Diana Rose D. Mamawal; Jonah David V. Calayo; Kherson P. Gandola; Mae Ashley G. Nacario; Mark Raymond A. Vejano; Laurice Beatrice Raphaelle O. dela Peña; Windell L. Rivera (IWA Publishing, 2023)
The extended-spectrum β-lactamase (ESBL)-producing Escherichia coli is becoming a global public health concern. More comprehensive surveillance of β-lactam resistance in E. coli would improve monitoring strategies and control resistance transmission in contaminated environments. This study investigated the prevalence of β-lactamase genes in E. coli isolated from the Seven Crater Lakes in San Pablo, Laguna, Philippines. Water samples from lakes were collected for the isolation of E. coli (n = 846) and molecular characterization by detecting the presence of the uidA gene. The isolates were then tested for the presence of β-lactamase genes using PCR. Among the screened genes, blaAmpC was the most dominant (91%). Other β-lactamase genes such as blaTEM, blaSHV, and blaCTXM were also detected with percentage occurrence of 34, 5, and 1%, respectively. Multiple genes within individual isolates were also observed, wherein blaTEM/AmpC was the most prevalent gene combination. Moreover, a significant negative correlation between blaAmpC with blaSHV and blaCTXM was depicted in this study. Overall, these findings demonstrate the presence of β-lactamase genes in E. coli in the Seven Crater Lakes of San Pablo and can be used in developing effective strategies to control antibiotic resistance in environmental waters. HIGHLIGHTS blaAmpC was the predominant gene detected among the five screened β-lactamase genes.; A significant association was detected between blaAmpC with blaSHV and blaCTXM.; blaKPC was not detected in any E. coli isolates from the lakes.; Seasonal variations have an effect on the fecal coliform counts and occurrence of β-lactamase-resistant E. coli isolates.;